Iliac Vein Compression Syndrome due to Bladder Distention Caused by Urethral Calculi - Akiko Ikegami; Takeshi Kondo; Tomoko Tsukamoto; Yoshiyuki Ohira; Masatomi Ikusaka (Case Reports in Urology)
We report a rare case of iliac vein compression syndrome caused by urethral calculus. A 71-year-old man had a history of urethral stenosis. He complained of bilateral leg edema and dysuria for 1 week. Physical examination revealed bilateral distention of the superficial epigastric veins, so obstruction of both common iliac veins or the inferior vena cava was suspected. Plain abdominal computed tomography showed a calculus in the pendulous urethra, distention of the bladder (as well as the right renal pelvis and ureter), and compression of the bilateral common iliac veins by the distended bladder. Iliac vein compression syndrome was diagnosed. Bilateral iliac vein compression due to bladder distention (secondary to neurogenic bladder, benign prostatic hyperplasia, or urethral calculus as in this case) is an infrequent cause of acute bilateral leg edema. Detecting distention of the superficial epigastric veins provides a clue for diagnosis of this syndrome.